EVALUATION OF THE IMPLEMENTATION OF THE AL-QUR'AN TAHFIDZ PROGRAM AT EMIISC ELEMENTARY SCHOOL, EXCELLENT METROPOLITAN INTEGRATED ISLAMIC SCHOOL JAKARTA - ZAMROJI, Isma'il Shiddiq; GHANI, Abd. Rahman A.; ISTARYATININGTIAS, Istaryatiningtias (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2024)
The research evaluates the implementation of the Tahfiz Al-Qur'an 3 Juz Mutqin program at SD EMIISc Jakarta using the CIPP evaluation model, which includes Context, Input, Process, and Product aspects, and applies a qualitative approach. Data collection was conducted through in-depth interviews with school stakeholders such as the principal, tahfiz coordinator, halaqoh teachers, and administrative staff, as well as through documentation and observation. The collected data was analyzed using the Miles and Huberman model, involving data reduction, data presentation, and conclusion drawing. The findings reveal that the context evaluation focuses on the program's philosophical foundation, mission, objectives, the process of vision and mission formulation, and the urgency of implementing the program. The input evaluation assesses leadership, the tahfiz curriculum, halaqoh teachers, student readiness, funding, and infrastructure support. The process evaluation examines planning, program execution, assessment standards, and monitoring activities. Lastly, the product evaluation measures outcomes such as the results of tahfiz exams, as well as academic and non-academic impacts on students. Overall, the evaluation concludes that the implementation of the Tahfiz Al-Qur'an 3 Juz Mutqin program at SD EMIISc Jakarta is effective and aligns well with the set evaluation standards, reflecting its success in achieving its goals.